2012
DOI: 10.4103/0250-474x.102538
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of amlodipine besylate, valsartan and hydrochlorothiazide in bulk mixture and tablet by UV spectrophotometry

Abstract: A simple, precise, accurate and economic simultaneous UV spectrophotometric method has been developed for the estimation of amlodipine besylate, valsartan and hydrochlorothiazide in combination in bulk mixture and tablet. The estimation was based upon measurement of absorbance at absorbance maxima of 359 nm, 317 nm and 250 nm for amlodipine besylate, hydrochlorothiazide and valsartan in methanol, respectively in bulk mixture and tablet. The Beer Lambert's law obeyed in the concentration range 5-25 μg/ml, 10-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…In this study, quinine showed detectable antibacterial activity against the three organisms used in the study with an MIC of 1,000 µg/mL against E. coli ATCC 25922, S. aureus NCTC 6571, and E. coli LLH029E. The MIC falls within the reported range of values (Kharal et al, 2009;Abreu et al, 2014). Our data show that quinine is bactericidal at 1,000 µg/mL and while this concentration is unlikely to be achieved physiologically during treatment, the additivity uncovered in this work indicates that lower concentrations may produce therapeutic effects in combination with antibacterials.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In this study, quinine showed detectable antibacterial activity against the three organisms used in the study with an MIC of 1,000 µg/mL against E. coli ATCC 25922, S. aureus NCTC 6571, and E. coli LLH029E. The MIC falls within the reported range of values (Kharal et al, 2009;Abreu et al, 2014). Our data show that quinine is bactericidal at 1,000 µg/mL and while this concentration is unlikely to be achieved physiologically during treatment, the additivity uncovered in this work indicates that lower concentrations may produce therapeutic effects in combination with antibacterials.…”
Section: Discussionsupporting
confidence: 64%
“…Of more interest is the fact that chloroquine and quinine have been reported to have some antibacterial activity, albeit at high concentrations, arising from their structural similarities to (Wolf et al, 2002;Lv et al, 2007;Davidson et al, 2008;Kharal et al, 2009;Bawa et al, 2010;Achan et al, 2011;Jagadeesh et al, 2014) quinolone antibacterials.…”
Section: Introductionmentioning
confidence: 99%
“…Amlodipine will selectively block the Ca2+ ion influx across the cell membrane. Thus, amlodipine will exert direct actions and effects on vascular smooth muscle [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analytical methods for their separation and quantification in pharmaceutical formulations and inhuman plasma are needed for quality control and therapeutic drug monitoring, respectively. Several techniques have been reported in the literature for determination of valsartan individually and combination with other drug other than atenolol [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] in pharmaceutical dosage forms or human serum samples. Atenolol (Fig.…”
Section: Introductionmentioning
confidence: 99%